Data Science and Big Data Analytics ACM-WIR 2018 - Mishra, Durgesh Kumar; Yang, Xin-She; Unal, Aynur (Lecture Notes on Data Engineering and Communications Technologies, 2019)
This book presents conjectural advances in big data analysis, machine learning and computational intelligence, as well as their potential applications in scientific computing. It discusses major issues pertaining to big data analysis using computational intelligence techniques, and the conjectural elements are supported by simulation and modelling applications to help address real-world problems. An extensive bibliography is provided at the end of each chapter. Further, the main content is supplemented by a wealth of figures, graphs, and tables, offering a valuable guide for researchers in the field of big data analytics and computational intelligence.